Experimental Study on Coconut Fibre Reinforced Self Compaction Concrete - Mohammad Meer; Akshay Sharma; Gaurav Wadhwani; Ashish Juneja (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Self-Compacting Concrete (SCC) has revolutionized the construction industry with its superior flowability, workability, and ability to consolidate under its own weight without the need for mechanical vibration. However, the brittleness and cracking susceptibility of traditional SCC remain significant concerns, especially in applications requiring enhanced durability and structural integrity. To address these challenges, the incorporation of natural fibres such as coconut fibres into SCC has emerged as a promising solution. Coconut Fibre Reinforced Self-Compacting Concrete (CFRSCC) is an innovative material that combines the advantages of SCC with the mechanical benefits of coconut fibres. Coconut fibres are abundant, renewable, and environmentally friendly, making them a sustainable choice for reinforcement. The addition of these fibres improves the tensile strength, ductility, and crack resistance of SCC, thus enhancing its overall performance. This study compares the properties of CFRSCC with traditional SCC, focusing on key parameters such as compressive strength, tensile strength, flexural strength, and durability. The results indicate that CFRSCC exhibits superior mechanical properties, including increased tensile and flexural strength due to the bridging effect of the fibres, which helps to arrest crack propagation and improve post-cracking behavior. Furthermore, the enhanced ductility of CFRSCC contributes to greater energy absorption and deformation capacity, making it more resilient under dynamic and impact loads. In terms of sustainability, CFRSCC leverages agricultural waste products, thereby reducing the reliance on synthetic fibres and contributing to waste management and environmental conservation. The utilization of coconut fibres also offers economic benefits, particularly in regions where coconut production is prevalent, by providing a value-added use for by-products that would otherwise be discarded. In conclusion, CFRSCC presents a superior alternative to traditional SCC by addressing its limitations and offering enhanced mechanical performance, sustainability, and economic advantages. This innovative material holds significant potential for a wide range of construction applications, promoting more durable, resilient, and eco-friendly infrastructure development.
Keywords: Self-Compaction Concrete; Coconut Fibre Reinforced Self-Compaction Concrete